ANALISIS WASTE PADA ALUR RUJUKAN PASIEN PELAYANAN PONED PUSKESMAS HALMAHERA KOTA SEMARANG DENGAN PENDEKATAN LEAN HEALTHCARE - Nurlita Putri Apriliani; Sutopo Patria Jati; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2017)
Central Java contributing the highest Maternal Mortality Rate in Indonesia,Semarang City is ranked the 2nd highest AKI in Central Java after BrebesRegency. Optimization of Basic Emergency Obstetric and Newborn Care (BEMONC) services is the government's effort to reduce MMR. HalmaheraHealth Center is the best PONED Puskesmas in Semarang city, but at servicecrotch is not optimal with 3 emergency referral case in dashboard entering red zone.Lean Healthcare is one of the concepts for quality management and cost efficiency to optimize value-oriented services. Qualitative includes 5 provinces  study with descriptive analytic approach was done at Halmahera Primary Health Care of Semarang. There was 9 informants in each PHC including Doctor, Midwife, Nurse and also patient's family. In depth interviews and observations was done to assesing waste in service process.Value Stream Mapping overview in the flow of patient referral services PuseksmasHalamheraBEMONC is ideal when viewed from the standard Response Time by Kepmenkes 856 in 2009. Results showed the ratio between the activities of the Value Added and Non-Value Added amounted to 36.36%; 63.64% which means the patient referral line of BEMONC service at Halmahera PHC is not yet in Lean condition. The types of waste found are unnecessary transportation, motion, waiting, defect, and underutilized abilities of people. The causes of problems that arise are the ethics and competence of the midwife, the layout of the room, supervision of leadership, clarity of division of labor, clarity of cooperation with vendors related sijariemas system, clarity of cooperation with CEMONC (Comprehensive Emergency Obstetric and Newborn Care) Hospital. Suggested changes to the layout of the room, clarity of cooperation with vendors and hospitals, increased supervision of the leadership, and the emergency drill routine to improve midwife competence.